Tunable geometric photocurrent in van der Waals heterostructure - Abdullah Rasmita (2022)
Utilizing the spin or valley degree of freedom is a promising approach for realizing more energy-efficient information processing devices. Circularly polarized light can be used to generate spin/valley current in monolayer 2D transition metal dichalcogenides. We observe a geometrically dependent photocurrent in heterostructure MoS2/WSe2, where light with a different circular polarization generates photocurrents in opposite directions. Furthermore, we show that this photocurrent persists even at room temperature, and it can be controlled using an in-plane electric field and back gating. We explain the observed phenomena via valley-dependent valence band shift and the valley optical selection rule. This finding may facilitate the use of 2D heterostructures as a platform for opto-valleytronics and opto-spintronics devices.